THE EUROPEAN MEDIA FREEDOM ACT: REGULATORY DEVELOPMENT AND IMPLEMENTATION CHALLENGES - Blagojević, Andrej (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2026)
Media regulation plays an essential role in safeguarding democracy and ensuring the proper functioning of the European Union’s internal market, as it secures the free flow of information, strengthens pluralism, and reduces risks of political and economic influence. These objectives lie at the core of the European Media Freedom Act (EMFA), the first binding EU legal framework dedicated to media freedom and pluralism. The paper examines the development of the EU media law framework and the context leading to the adoption of the EMFA, as well as the challenges that arise in its early implementation. It also traces the development of EU media law – from the Television Without Frontiers Directive, through the AVMSD, to the DSA/DMA package – which illustrates the rationale behind adopting a single regulation. The analysis provides an overview of the key regulatory aspects of the EMFA and assesses the challenges accompanying its implementation in the EU Member States.